Juvenile idiopathic arthritis - classification and methods of treatment - Weronika Pawłocik; Laura Wojtala; Weronika Pawlak; Julia Szymańska; Agnieszka Możdżyńska; Lena Musiał; Ewa Grabowska; Kamil Kapłon; Katarzyna Pacek; Izabela Kamińska (Kazimierz Wielki University, 2023)
Introduction Juvenile idiopathic arthritis (JIA) is the most common chronic rheumatic disease of unknown etiology that affect children. According to the definition of JIA, the disease begins before the age of 16 and lasts more than 6 weeks. The International League of Associations for Rheumatology (ILAR) has divided juvenile idiopathic arthritis into seven categories: systemic, oligoarticular, polyarticular RF (-), polyarticular RF (+), psoriatic, enthesitis-related and undifferentiated arthritis.   Purpose  The aim of this review is to present the classification, etiopathogenesis, diagnosis, treatment and complications of juvenile idiopathic arthritis. Methods  Literature searches in PubMed, Google Scholarship, and open source books were used to gather information. Results  Complex interactions between cells of the immune system are responsible for the pathophysiology of JIA and indicate the need to divide the disease into clinical subtypes, the heterogeneity of which requires different therapeutic actions. There are many groups of drugs with different mechanisms of action used in the treatment of JIA, including: T lymphocyte inhibitors, anti-TNFα, JAK inhibitors, IL-1 and IL-6 blockers. Despite the great progress and the commitment of scientists, there is still no treatment strategy to completely stop the development of the disease.   Conclusions   Scientific research conducted around the world has led to the recognition of numerous pathways leading to the formation of the inflammatory process and the symptoms of JIA. Knowledge of these mechanisms allows scientists to conduct research on further drugs, the aim of which is to find a treatment strategy that prevents permanent joint damage, improves treatment results, and enables sustainable remission. It is necessary to expand knowledge about the pathways responsible for the formation of the inflammatory process, the interruption of which would allow complete inhibition of the development of the disease.